Adjuvant chemotherapy of completely resected early stage non-small cell lung cancer (NSCLC) - Liang, Ying (Transl Lung Cancer Res, 2013)
Surgery is regarded as the primary treatment modality for early stage non-small cell lung cancer (NSCLC), but even after complete resection, a substantial percentage of these patients eventually develop local recurrence or distant metastases. Therefore more effective treatment strategies to reduce lung cancer mortality and recurrence rate are needed. Only recently has the use of adjuvant chemotherapy become standard in early stage NSCLC, at least for stage II and resected IIIA NSCLC. Controversies remain about the benefit for stage I patients. Five-year survival improvements of 5% to 10% have been reported with cisplatin-based adjuvant chemotherapy from multiple large randomized phase III clinical trials and meta-analyses. Questions remain as to which patients benefit and which regimens are best. In this paper, important clinical research in the field of adjuvant chemotherapy of NSCLC is reviewed.